The Standard Digital Agreement For Shopee Pay Later Users In Terms Of Consumer Protection Laws Perspective - Attamimi, Zeehan Fuad; Marsitiningsih; Nurul Aulia (Universitas Muhammadiyah Surakarta, 2024)
The technological landscape in Indonesia has rapidly evolved with the emergence of various platforms/applications utilized by Indonesian society. One of significant technological advancement in Indonesia is Financial Technology (Fintech). Fintech is a form of financial-based application with various service features. The service features within Fintech offer broader benefits and convenience to users under a single platform enhancing simplicity. Shopee PayLater (SPayLater) is one of the various types of Fintech in Indonesia. SPayLater is a service offered within the Shopee application. The service feature of SPayLater includes buyer-seller transactions facilitated using installment payment methods according to specified periods. This article differs from others that solely discuss conventional commercial transactions, as it specifically examines transactions enabled by Fintech. The methodology employed in this article adopts a normative juridical research approach, incorporating legislative analysis presented in a descriptive-analytical narrative format. The results of this study indicate that transactions involving installment payments are formalized through a standardized agreement, a type of contract unilaterally prepared by SPayLater as the service provider, without any bargaining position. This arrangement may lead to an imbalance contrary to the principle of balanced agreements. The inclusion of exoneration clauses within standard agreements could potentially disadvantage users. Therefore, consumer protection measures are necessary to oversee service providers, who are the architects of contract clauses, in compliance with consumer protection laws as a form of reactive approach. Additionally, introducing agreement features involving user participation in negotiations with service providers is essential to establish a balanced bargaining position, ultimately ensuring equitable agreements as a preventive measure. Lanskap teknologi di Indonesia telah berkembang pesat dengan munculnya berbagai platform. Salah satu kemajuan teknologi yang cukup signifikan di Indonesia adalah financial technology (Fintech). Fintech merupakan salah satu bentuk aplikasi berbasis keuangan dengan berbagai fitur layanan. Shopee PayLater (SPayLater) merupakan salah satu dari berbagai jenis fintech yang ada di Indonesia. SPayLater adalah layanan yang ditawarkan dalam aplikasi Shopee. Fitur layanan dari SPayLater antara lain transaksi pembeli-penjual yang difasilitasi dengan metode pembayaran cicilan sesuai periode yang ditentukan. Artikel ini berbeda dengan artikel lain yang hanya membahas transaksi komersial konvensional. Tujuan dari penulisan artikel ini adalah untuk mengulas perjanjian baku pada transaksi yang dilakukan oleh Fintech dan penggunanya dari sudut pandang Undang-Undang Perlindungan Konsumen. Metodologi yang digunakan dalam artikel ini menggunakan pendekatan penelitian yuridis normatif. Hasil penelitian ini menunjukkan bahwa transaksi yang melibatkan pembayaran cicilan diformalkan melalui perjanjian baku, yaitu jenis kontrak yang dibuat secara sepihak oleh SPayLater sebagai penyedia layanan, tanpa adanya posisi tawar-menawar. Pengaturan ini dapat menimbulkan ketidakseimbangan yang bertentangan dengan asas perjanjian yang seimbang. Pencantuman klausula eksonerasi dalam perjanjian baku berpotensi merugikan pengguna. Oleh karena itu, langkah-langkah perlindungan konsumen diperlukan untuk mengawasi penyedia layanan, yang merupakan arsitek klausul kontrak, agar sesuai dengan undang-undang perlindungan konsumen sebagai bentuk pendekatan reaktif. Selain itu, fitur perjanjian yang melibatkan partisipasi pengguna dalam negosiasi dengan penyedia layanan sangat penting untuk membangun posisi tawar yang seimbang, yang pada akhirnya memastikan perjanjian yang adil sebagai tindakan pencegahan.